Increasing the Effectiveness of Interpersonal Communication through Understanding and Strengthening Self-Concept - OK Dedy Arwansyah; Agung Suharyanto (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to enhance the effectiveness of interpersonal communication through understanding and strengthening self-concept. Effective interpersonal communication is a crucial skill in human life, contributing to building meaningful relationships, fostering trust, and resolving conflicts. However, a weak self-concept often hinders effective communication, such as low self-esteem or social anxiety. This research highlights that a positive self-concept is key to boosting confidence, openness, and empathy, essential elements in social interactions. In increasingly complex cross-cultural communication, a strong self-concept is the foundation for adapting to diverse social backgrounds. The study emphasizes the importance of self-acceptance, feedback management, and motivation for personal growth as primary components in enhancing interpersonal communication skills. These findings provide insights into how individuals can build more harmonious and constructive relationships by managing a healthy self-concept effectively.